Perlindungan Hak Asasi Manusia dalam Kasus Diskriminasi Gender - Winda W. Ndolu; Saryono Yohanes; Jenny Ermalinda (Mahkamah : Jurnal Riset Ilmu Hukum, 2024)
This study aims to find out and analyze the protection of human rights in cases of gender discrimination. This research is a normative legal research using a statue approach, conceptual approach, historical approach and case approach. This research is a research using primary, secondary and tertiary legal materials obtained using literature study techniques. The results of the study show that (1) the form of handling gender discrimination in Indonesia can be carried out by state institutions related to gender discrimination such as the Ministry of Women's Empowerment and Child Protection and the National Commission on Anti-Violence against Women. (2) There are several factors driving gender discrimination in Indonesia, including economic factors, cultural and social factors, legal factors and educational factors.